1995
DOI: 10.1111/j.1432-1033.1995.563_b.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Transthyretin–Retinoic‐Acid Complex

Abstract: Retinoids are quite insoluble and chemically unstable compounds in thc aqucous mcdium, such that natural retinoids nccd to be bound to specific retinoid-binding protcins to be protected, solubilized and transported in body fluids. All-tmns retilioic acid exhibits a relatively high affinity for thyroxine-binding transthyretin irz vitm and this protein is a good candidate for the transport of retinoic acid adn~iniskred us pharmacological or antitumor agent. To dcfitic structural features esseniial for the recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 27 publications
1
32
1
2
Order By: Relevance
“…Thus, the retinol hydroxyl group may significantly contribute to the strength of binding of the vitamin to the protein. This is in agreement with the results of competition binding experiments showing a lower binding affinity of retinoids for RBP as compared with retinol (Berni R., unpublished results) and with structural data for the binding of retinol analogs to RBP (Zanotti, Malpeli et aL, 1993;Zanotti et al, 1994). The non-perfect planarity of the rest of the tail, and in particular of the last two C atoms, may be attributed to the constraints imposed by the protein side chains and by the very limited space available in the fl-barrel cavity.…”
Section: The Rbp-bound Retinol Moleculesupporting
confidence: 87%
“…Thus, the retinol hydroxyl group may significantly contribute to the strength of binding of the vitamin to the protein. This is in agreement with the results of competition binding experiments showing a lower binding affinity of retinoids for RBP as compared with retinol (Berni R., unpublished results) and with structural data for the binding of retinol analogs to RBP (Zanotti, Malpeli et aL, 1993;Zanotti et al, 1994). The non-perfect planarity of the rest of the tail, and in particular of the last two C atoms, may be attributed to the constraints imposed by the protein side chains and by the very limited space available in the fl-barrel cavity.…”
Section: The Rbp-bound Retinol Moleculesupporting
confidence: 87%
“…It has been observed that TTR, like albumin, is quite promiscuous in its binding to small molecules. The range of structures that are competent as amyloid fibril formation inhibitors has been alluded to above; it has also been found in unrelated studies that TTR binds to aurones, 37 bipyridines, 35 retinoic acid (even without the intermediacy of retinol binding protein), 52 and various organic halogen substances (OHS). 34,[53][54][55][56] In fact, it has been suggested that TTR transports polychlorinated biphenyls in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesize that these aromatic residues, which are absent in transthyretin, could account for the difference in thyroxine binding affinity displayed by the two proteins. In 1995, the laboratory of Zanotti [62] determined the crystal structure of a complex of transthyretin with retinoic acid. The retinoid fits into the two chemically identical thyroxine-binding sites.…”
Section: Further Studies On Thyroxine Bindingmentioning
confidence: 99%